The Influence of 'Maro' Profit-Sharing System through Farmers’s Welfare - Yuni Shafira Rahmah; Syihabudin Syihabudin; Kheryadi Kheryadi (FEB Universitas Sultan Ageng Tirtayasa, 2019)
The aims of this study was to determine whether the system is divided 'maro' results affect the income of farmers and also to find out the difference in income for results before and after using the 'maro' profit sharing system. The method of research used is quantitative research. The approach uses the survey method. Based on the results of the analysis obtained from the hypothesis test done by comparing t arithmetic with t table which is shows that t arithmetic of 16.207> from t table of 2.639 and a significance level of 0,000 <0.005 this shows that Ho rejected and Ha accepted which means that there is a positive influence between 'maro' profit-sharing systemt through income of the farmers. Figures for the coefficient of determination performed on the test Determination is obtained R square adjust value of 0.746. It means that the profit sharing system affects welfare society by 74.6%.